Molecular identification, early development and distribution of larval blunthead puffer Sphoeroides pachygaster (Teleostei: Tetraodontidae) off southeastern Brazil - Henrique Grande; Ana C. T. Bonecker; Mariana M. Julio; Mario Katsuragawa; Maria de Lourdes Zani-Teixeira; Mateus G. Chuqui; Artur R. Spirgatis; Gabriela B. França; Frederico P. Brandini; Cláudia A. P. Namiki (Neotropical Ichthyology)
Abstract We studied the early larval stages (preflexion and flexion) of the pufferfish Sphoeroides pachygaster based on ichthyoplankton samples collected off the southeastern coast of Brazil. Species identification was performed through molecular analysis and morphological, morphometric, and meristic characters of different larval development stages. A total of 4,077 specimens were collected, with the vast majority (4,071 larvae) in the preflexion stage and the remainder (6 larvae) in the flexion stage. These larvae have a robust body shape, moderate height (body depth = 35.8% of the body length in early preflexion and 33.9% in flexion), and large eyes (eye diameter = 48.6% of the head length in preflexion and 36.8% in flexion stage). The tail is longer at the beginning of the preflexion stage (approximately 45% of body length at 1.53 mm). It decreases in length during the flexion stage (approximately 20% of body length at 6.43 mm). Notochord flexion initiates at around 5.69 mm and continues until at least 6.43 mm. The first observation of body inflation was recorded in a larva measuring 5.98 mm. Sphoeroides pachygaster larvae have a wide distribution across the study area, ranging from the outer shelf to oceanic waters. Vertically, the species is predominantly found within the water column layers between 0 and 50 m in depth.